ANALYSIS OF KAHOOT UTILIZATION IN LEGAL SYSTEM TOPICS IN INDONESIA FOR CIVIC EDUCATION COURSES - Umam, Fahrurrizal; Murdiono, Mukhamad; Charismana, Dian Satria (International Journal of Social Service and Research, 2025)
This article aims to analyze the effectiveness of the use of Kahoot in teaching material about the Indonesian legal system in the Civic Education course. The study was conducted in the Bachelor of Accounting Study Program, Study Group-C, Faculty of Economics, Yogyakarta State University. This study used a qualitative method, with data collection techniques in the form of observation and interviews. The number of participants in this study was 53 students, which was the main focus in the process of collecting and analyzing data related to the use and use of kahook in Civic Education learning in the legal system material in Indonesia. The results showed that students were excited about the learning process and showed high enthusiasm for the learning experience. The use of interactive technology in learning is able to provide a fun and meaningful learning experience, which supports the achievement of learning goals regarding effective law enforcement in Indonesia, thereby contributing to effective pedagogical strategies for Civic Education.